2021
DOI: 10.2174/2211536610666210604122816
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of MicroRNA 21 in Endometrial Cancer and Benign Lesions and its Differential Expression with Clinicopathological Parameters

Abstract: Background: Endometrial cancer is one of the most common malignancies among women worldwide. Although this cancer is often diagnosed at early stages, the need for biomarkers of diagnosis remains a necessity to overcome conventional invasive procedures of diagnosis. Objective: In our study, we aim to investigate the diagnostic value of microRNA-21 in endometrial cancer and its relation to clinicopathological features. Methods: We used RT-qPCR to measure the expression of microRNA-21 in 71 tumor tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Bouziyane et al demonstrated the high diagnostic efficacy of miR-21-5p in their research. This study included a large group of 71 endometrial cancer tissues, 53 adjacent tissues, and 54 benign lesions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bouziyane et al demonstrated the high diagnostic efficacy of miR-21-5p in their research. This study included a large group of 71 endometrial cancer tissues, 53 adjacent tissues, and 54 benign lesions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that ECs with high levels of miR-21 expression had advanced tumor stages, high histological grades, cervical invasion, myometrial invasion, and distant metastasis [ 52 ]. As a result, miR-21 might be used as a biomarker to identify benign lesions from ECs [ 52 ]. MiR-21 has been shown to promote the growth of esophageal carcinoma [ 53 ], melanoma [ 54 ], and cervical cancer [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the review of exosomal biomarkers, 15 studies were eligible for inclusion, and these reported on 29 different exosomal biomarkers and a total of 5527 patients. Amongst this group 2530 had a diagnosis of EC and 2456 were non-cancerous control-group patients [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Only Mi-RNA 21, 27a, and 223 were suitable for meta-analysis as they met the inclusion criteria and were reported by two or more studies.…”
Section: Discussionmentioning
confidence: 99%
“…The control groups consisted of healthy women with normal endometrium as well as those with benign endometrial lesions such as polyps and fibroids. Only studies of micro-RNA 21, 27a, and 223 were suitable for meta-analysis after meeting the inclusion criteria [29][30][31][32][33][34][35]. None of the included studies reported positive predictive values (PPV) or negative predictive values (NPV) (Table 1).…”
Section: Meta-analysis Of Exosomal Biomarkersmentioning
confidence: 99%